The enchantment sphere: a non-dualistic approach to singularization and commoditization - Pompeo, Karin Ligia Brondino (2017)
Dualistic interpretations of Kopytoff’s commoditization process prevail in consumer research literature. In those studies, the object is either a commodity or a singularized possession, ignoring the author’s original approach in which several exchange spheres, with different levels of singularization, can coexist. This research offers a closer account to the original approach by: 1) highlighting the theoretical extensions as well as the misinterpretation so far; 2) investigating some of the spheres that can exist in the ‘gray zone’ between the two ideal polar types of singularization and commoditization, and 3) proposing a new framework of the commoditization-singularization process for consumer studies. To achieve these, I developed a comprehensive analysis of how singularization and commoditization concepts appear in consumer research literature, interviewed consumers in four different countries, immersed myself in several activities to understand their context, and traced the biography of an object: the vintage Selmer Mark VI saxophone. The chosen sphere for a deeper analysis I named the enchantment sphere, since the objects within it radiate a transcendent allure that obliterates objective explanations for its superior qualities. The objects within this sphere are a clear example of the ambiguous state of a commodity as advocated by Kopytoff, because they experience at the same time some level of singularization and some level of commoditization. This is possible because those objects are precluded from extreme commoditization due to their magical allures, while still having an evident exchange value. Considering the findings that result both from the literature analysis and the fieldwork, I propose a cohesive visual concept that explains the commoditization-singularization process as a non-linear structure and that also allows further complements and extensions.